Privacidade no sistema Android - Borges, Daniel (2015)
Computational development has, in recent years, led to a massive spread of mobile devices, these devices are highly evolved not only computationally as also in the ability to access and store all types of data, thus, the possibility of system or privacy attacks increases. Android is among the most used operating systems on mobile devices, with a very significant market share. This system takes advantage of using open source software, relying with a tremendous evolution, however, as in all operating systems, it is necessary to adapt and upgrade it to meet the market demands. With regard to security, Android has some flaws and this added to the number of ordinary users constantly increasing or the need to adapt the system security to a enterprise level, is required to make Android more secure, building mechanisms to ensure user’s privacy. This operating system allows to install applications from a variety of sources, this, and free applications, often implies costs to the user’s privacy since these applications access the private resources that do not require. The aim of this work is to study mechanisms of confinement and illusion offering individual and efficient control over which applications access certain content or physical resource. For this purpose, we create a false profile but coherent and as realistic as possible, granting or denying access to the data we want to applications that attempt to access private information without the need for their normal functioning.